1988
DOI: 10.1136/pgmj.64.754.617
|View full text |Cite
|
Sign up to set email alerts
|

Haematological, neurological and psychiatric complications of chronic hypothermia following surgery for craniopharyngioma

Abstract: Summary:A patient is described who became poikilothermic following surgery for removal of a craniopharyngioma. Episodes of disturbed behaviour, neurological abnormilities, pancytopenia and deranged liver function could be correlated with episodes of more profound hypothermia on a background of a chronically lowered core temperature. The association of pancytopenia and neuropsychiatric disturbances with hypothermia is discussed with reference to reported cases of periodic spontaneous hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
(1 reference statement)
0
17
0
Order By: Relevance
“…8 Generally speaking, there are two ways of inducing brain hypothermia: by systemic (whole-body) cooling and local (selective) cooling. Owing to the confirmed severe adverse complications, such as shock on rewarming, increased cardiac ischaemia perioperatively and a tendency to bleed even with a normal haemostatic test in patients receiving MSH, 9 SBC has been investigated and applied in clinical studies to maximize neuroprotection while minimizing systemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…8 Generally speaking, there are two ways of inducing brain hypothermia: by systemic (whole-body) cooling and local (selective) cooling. Owing to the confirmed severe adverse complications, such as shock on rewarming, increased cardiac ischaemia perioperatively and a tendency to bleed even with a normal haemostatic test in patients receiving MSH, 9 SBC has been investigated and applied in clinical studies to maximize neuroprotection while minimizing systemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (31) reported absence of thirst in 19% of adults with DI treated with surgery combined or not with CRT. A loss of temperature control (very low temperature) was recorded in adult CP patients after surgery for a CP (32). Somnolence is common in adult CP patients and in the majority due to sleep apnoea (33), and disorders of sleep pattern and excessive daytime sleepiness have been recorded in up to one-third of adult CP patients (34).…”
Section: Thirst Disorder Thermoregulatory Disorders Somnolence and mentioning
confidence: 99%
“…Primary and metastatic brain tumors may cause hypothermia. [4,[12][13][14][15] Autonomic neuropathy was suggested to define the role of the autonomic nervous system by the authors. [5,9] Another view is that the different drugs are associated with hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, this clinical manifestation has been reported from several case reports. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Herein we presented a case of stage IIIB Hodgkin's disease, complicating with hypothermia and hypotension after naproxen sodium administration.…”
mentioning
confidence: 99%